Corruption in Bank Lending: The Role of Timely Loan Loss Provisioning - ATKINS, B (Institutional Knowledge at Singapore Management University, 2015)
Building on the recent literature on corruption in bank lending, we examine the effect of country-level timely loan loss provisioning by banks on such corruption using a unique World Bankdataset that covers more than 3,600 firms across 44 countries. We find evidence consistent with timely loan loss provisions constraining lending corruption because it increases the likelihood of problem loans being uncovered earlier. This result is robust to using the tax-deductibility of loan loss provisions as an instrumental variable. In further analysis, we find timely loan loss provisioning less associated with reduced corruption in countries with deposit insurance schemes and significant government ownership in the banking system. This evidence is consistent with timely loan loss provisioning being less of a deterrent on lending corruption when banks are less disciplined by their capital providers (depositors and investors).